Preventing lawful and decent burial: resurrecting dead offences. (June 2016) - Jones, Imogen; Quigley, Muireann
Abstract : Recent high‐profile convictions have called attention to the common law offence of preventing a lawful and decent burial. This offence, which can only be found in its modern incarnation since 1974, is being used with increasing frequency. We argue that there is, however, little justification (or need) for criminalising the prevention of burial per se. The historical context of the need to regulate the disposal of corpses is no longer relevant. Moreover, the ambit of the offence is such that it cannot be argued to be targeting acts of intentional disrespect to deceased bodies. We suggest that acts which intentionally impede the administration of justice are rightly criminal, but other offences already deal more appropriately with these. We conclude that the contemporary use of the offence of preventing a lawful and decent burial contributes to an unnecessary proliferation of overlapping offences, providing prosecutors and juries with a way to assign liability to a person whom they suspect, but cannot prove, is guilty of more serious charges.